(untitled) - Behme, Stefan (Weinheim, Germany, 2009)
This comprehensive introduction covers all aspects of biopharmaceutical manufacturing, including technology and facilities, GMP and regulatory issues, as well as costing and timeline aspects for supply chain implementation. Written by a leading expert at one of the largest pharmaceutical companies worldwide, this practical text is aimed at a wide audience ranging from libraries, biotech companies to students and technicians planning to enter biopharmaceutical manufacturing. In addition, it is well suited for academic teaching as well as internal training within larger biotech or pharmaceutical companies.
Keywords: Protein drugs,Pharmaceutical industry,Drug Industry,Proteins,Proteins; Economics,Chemical synthesis,Therapeutic use